Potential of anionic-nonionic surfactant mixtures for oilwell contaminated drillcuttings washing - Muherei, M. A.; Junin, Radzuan (2007)
Surfactant-enhanced washing is being considered with increasing frequency to achieve contaminant removal. However, sorption of nonionic surfactants by soil surfaces such as clay minerals and/or organic matter content and abstraction of anionic surfactant by multivalent cations may negate their contaminant extraction efficiency. In this research anionic (SDS), nonionic (TX100) and their mixtures (1:1, 1:2, 2:1; TX100:SDS volumetric ratios) were evaluated for the washing enhancement of oilwell contaminated drillcuttings. Evaluation of surfactants are based on examining the ability of the surfactant to maintain lower surface tensions (ST), lower interfacial tensions (IFT) between Sarapar l47 and water, satisfying lower critical micelle concentrations (CMCs), and sustaining lower sorption to drillcuttings. Interaction between binary surfactant mixtures were studied by surface and interfacial tensions. The composition of mixed micelles and the interaction parameter, β evaluated from the CMC data obtained by both surface and interfacial tensions for different systems using Rubingh’s theory were discussed. Using IFTs to determine CMCs before and after equilibration with shale (drillcuttings surrogate) gave different results than using ST technique. Considering ST technique, it has been concluded that presence of SDS do not reduce sorption of TX 100 to shale and that the binary mixtures of SDS and TX 100 do not show any synergism. However, IFT technique measurements allow opposite conclusions, i.e., sorption of TX 100 was significantly reduced by addition of SDS at all molar ratios used in this study. Furthermore, SDS: TX100 mixtures showed a strong synergism particularly in CMCs. The estimated interaction parameters indicate an overall attractive interaction in the mixed micelles.